Population Genetic Structure at the Northern Edge of the Distribution of Alexandrium catenella in the Patagonian Fjords and Its Expansion Along the Open Pacific Ocean Coast - Paredes, Javier; Varela, Daniel; Martínez, Camila; Zúñiga, Andrea; Correa, Karen; Villarroel, Adrián; Olivares, Bianca (Frontiers in Marine Science, 2019)
In southern Chile, Alexandrium catenella is the main species generating HABs and over time it has expanded its range since it was first recorded in the Magallanes region in 1972. In 2016 a severe bloom of an Alexandrium species occurred, which was notable for its intensity and geographical extent, extending into new areas to the north of the Patagonian fjords including areas along the open Pacific Ocean coast. Given the exceptional nature of this event, we verified the taxonomic classification of the species that generated the bloom and evaluated the influence of the range expansion process on its genetic structure and population diversity. This was achieved by isolating clones collected in 2014 from cyst beds located at the northern limit of its then known distribution, along with clones isolated from the water samples taken during the 2016 bloom. These clones were characterized genetically with LSU rDNA and AFLPs molecular markers. Phylogenetic analyses showed that all clones were aggregated in the Group I of the A. tamarense species complex, which confirmed that A. catenella was the species responsible for the 2016 bloom. High genetic diversity was observed within populations though there were no significant differences between populations. Furthermore, genetic structure showed an isolation by distance relationship among populations, and several analyses consistently indicated a high divergence among the population groups derived from both cysts and vegetative cells. Despite this study not finding the patterns expected for species range expansion (i.e. diversity gradient and/or high population divergence), the genetic diversity and structure indicated that these were influenced by the geographic distance effect and the physical restrictions to gene flow, along with the demographic processes that occurred during the distinct phases of the life cycle of A. catenella.